Carbonic Anhydrase Inhibitors from Marine Natural Products - Claudiu T. Supuran (Marine Drugs, 2022)
Carbonic anhydrases (CAs, EC 4.2.1.1) are widespread metalloenzymes in organisms in all life kingdoms, being involved in pH regulation, metabolic processes and many other physiological and pathological conditions. CA inhibitors and activators thus possess applications as pharmacological agents in the management of a range of diseases. Marine natural products have allowed the identification of some highly interesting CA inhibitors, among which are sulfonamides, phenols, polyamines, coumarins and several other miscellaneous inhibitors, which are reviewed here. Psammaplin C and some bromophenols were the most investigated classes of such marine-based inhibitors and have been used as lead molecules for developing interesting types of potent and, in some cases, isoform-selective inhibitors, with applications as antitumor agents by inhibiting human CA XII and P-glycoprotein activities. Some phenols have shown interesting bacterial and fungal β-CA inhibitory effects. Marine natural products thus constitute a gold mine for identifying novel CA inhibitors, some of which may lead to the development of novel types of pharmacological agents.